2021
DOI: 10.1002/jclp.23138
|View full text |Cite
|
Sign up to set email alerts
|

Childhood emotional abuse and problematic social networking sites use in a sample of Italian adolescents: The mediating role of deficiencies in self‐other differentiation and uncertain reflective functioning

Abstract: Objective: Childhood emotional abuse (CEA) is associated with various negative mental health outcomes. This study aimed to investigate the association between CEA and problematic social networking site (SNS) use in a sample of Italian adolescents.Design: Using structural equation modeling, the study examined whether the relationship between CEA and problematic SNS use was sequentially mediated by self-other differentiation and uncertain reflective functioning in 1308 Italian adolescents (628 males, age range 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 114 publications
2
30
0
1
Order By: Relevance
“…Marino et al [ 32 ] found that motives with negative valences, such as coping (i.e., using SNS to reduce negative affect) and conformity (i.e., using SNS to avoid social rejection), were more closely related to problematic Facebook use than motives with positive valences, such as enhancement (i.e., using SNS to increase positive affect) and social (i.e., using SNS to improve relationships with friends). Consistent with the theory of compensatory Internet use [ 27 ], a vicious cycle may start with the person spending time on SNSs to temporarily escape from unpleasant feelings or events related to offline problems, and this, in turn, may exacerbate the sense of being unable to cope with daily difficulties [ 35 ]. In addition, findings of a recent study by Balcerowska and Sawicki [ 28 ] on 1659 SNSs users showed that compensatory mechanism is specific for narcissistic vulnerability, whereas other forms of narcissism may be linked with PSNSU in other ways (i.e., via antagonism and hostility towards others in the case of rivalrous narcissism).…”
Section: Introductionmentioning
confidence: 99%
“…Marino et al [ 32 ] found that motives with negative valences, such as coping (i.e., using SNS to reduce negative affect) and conformity (i.e., using SNS to avoid social rejection), were more closely related to problematic Facebook use than motives with positive valences, such as enhancement (i.e., using SNS to increase positive affect) and social (i.e., using SNS to improve relationships with friends). Consistent with the theory of compensatory Internet use [ 27 ], a vicious cycle may start with the person spending time on SNSs to temporarily escape from unpleasant feelings or events related to offline problems, and this, in turn, may exacerbate the sense of being unable to cope with daily difficulties [ 35 ]. In addition, findings of a recent study by Balcerowska and Sawicki [ 28 ] on 1659 SNSs users showed that compensatory mechanism is specific for narcissistic vulnerability, whereas other forms of narcissism may be linked with PSNSU in other ways (i.e., via antagonism and hostility towards others in the case of rivalrous narcissism).…”
Section: Introductionmentioning
confidence: 99%
“…Like attachment security, RF is important in a person’s sense of self, as demonstrated by its negative relationship with borderline personality disorder [ 26 , 28 ]. Impairment in RF also may be implicated in other mental health problems, including psychosis, mood and anxiety disorders [ 29 ] and addictive behaviors [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature on collective/social traumatic events (e.g., Eriksson, 2015 ; Neubaum et al, 2014 ) showed that in disaster contexts, social media can be useful for social regulation and information sharing. Nonetheless, during COVID-19 social media also contributed to spreading panic (Ahmad and Murad, 2020 ), and in some cases, the fear of “missing out” and becoming “socially invisible” resulted in excessive use of online social interactions (Gioia et al, 2021 ), showing a dual-sided connotation of social media engagement as both able to foster relational closeness and alleviate social panic (Wiederhold, 2020 ; Cauberghe et al, 2021 ; Musetti et al, 2021 ) and as a maladaptive behaviour leading to increased levels of anxiety and negative affect contagion (Boursier et al, 2020 ; Shao et al, 2021 ).…”
mentioning
confidence: 99%